Estimation of economic burden of high salt intake in cardiovascular disease attributed to hypertension in Iran - Sirous Pourkhajoei; Reza Goudarzi; Mohammadreza Amiresmaeili; Nouzar Nakhaee; Vahid Yazdi-Feyzabadi (Cost Effectiveness and Resource Allocation)
Abstract Background Excessive salt consumption is a significant risk factor for the development of cardiovascular disease (CVD) attributed to hypertension, major contributors to mortality in Iran. This study aims to estimate the economic burden of high salt consumption on CVD attributed to hypertension in Iran in 2022. Methods The cross-sectional research was conducted in public and private hospitals in the southeast of Iran. The costs of CVD patients attributed to hypertension (ICD I10-I15) were estimated using a prevalence-based and bottom-up approach from society’s perspective classifying costs into direct and social Costs of disease management. The indirect costs of productivity losses were quantified using the human capital approach. Sensitivity analysis was employed to investigate the effect of uncertain parameters. Results The mean cost per CVD patient was US$1392.48, with an estimated total economic burden of US$980.61 million in Iran. Direct costs constituted 44.47% of the total disease burden, while social costs accounted for 55.53%. The results were robust, with a 20% variation in the average unit price of all direct medical and non-medical costs. Conclusion The study highlights the substantial economic burden of high salt consumption on CVD attributable to hypertension in Iran, amounting to 3.25 times current health expenditures per capita and 0.27 times GDP per capita in 2022. Indirect costs, including productivity losses, surpass direct costs, underscoring the broader societal impact. Sensitivity analysis confirms the robustness of results, emphasizing the urgent need for preventive measures and resource allocation. Policymakers are encouraged to prioritize salt reduction programs to mitigate costs, enhance patient care, and promote long-term economic and health benefits.